Secret of the white rose - Pintoff, Stefanie. (Minotaur Books, 2011)
"The murder of Judge Hugo Jackson is out of Detective Simon Ziele's jurisdiction in more ways than one. It's high profile enough to command the attention of the notorious new police commissioner, since Judge Jackson was presiding over the sensationalist trial of Al Drayson. Drayson, an anarchist, set off a bomb at a Carnegie wedding, but instead of killing millionaires, it killed passersby, including a child. Furthermore, Simon's assigned precinct on Manhattan's west side includes the gritty Tenderloin but not the tonier Gramercy Park, which is where the judge is found in his locked townhouse with his throat slashed on the night before the jury is set to deliberate. But his widow insists on calling her husband's old classmate criminologist Alistair Sinclair, who in turn enlists Ziele's help. Together they must steer Sinclair's unorthodox methods past a police force that is so focused on rounding up Drayson's supporters that they've all but rejected any other possibilities. Once again, Pintoff 's combination of vital characterizations and a fascinating case set amongst the sometimes brutal and sometimes glittering history of turn-of-the-century New York makes for totally compelling reading"--